Strategy for the Resumption of On-Site Operation of the University of Ghana Library System Amid the Corona Virus Pandemic - Donkor, Antonia Bernadette; Yeboah, Francis; Afrane, Daniel Akwasi (International Association of University Libraries (IATUL, 2020), 2020)
The availability of information on the nature and spread of the Corona Virus eased the fear and uncertainties surrounding the pandemic after about three months episodes of total and partials lockdowns in Ghana. This saw the government of the Republic of Ghana gradually easing restrictions imposed on citizenry. After nearly three months (90 days) of the closure of the University of Ghana, and for that matter the Balme Library, a hint from the President on the possible re-opening of schools and stakeholder engagements with tertiary institutions sparked up the interest of librarians in looking out for possible re-opening strategies. A purposeful sample of nine senior members was drawn from the population of Senior Members who support the managerial operations of the library. This sample comprised the Reference Librarian and the Head of the various Satellite Libraries in the University of Ghana Library System (UGLS). Through focus group discussions, using virtual platforms such as Zoom and WhatsApp a plan for the safe occupancy of the Libraries was put together to be implemented should the University be called to resume its teaching activities. This paper examines the strategies employed in developing the strategic plan that was implemented for the safe resumption of on-site operation by UGLS amid the Covid-19 pandemic in June, 2020.
Abstract
Keywords: On-Site Operation, University of Ghana Library System, Corona Virus Pandemic